Behavior of Using Tax Technology in Tax Volunteers in Jember Regency - Sandi, Anisaul Fadila; Probowulan, Diyah; Zulkarnnaeni, Achmad Syahfrudin (Westscience Press, 2024)
This study aims to determine the behavior of using tax technology in tax volunteers in Jember district. This study compares whether there is a difference in the behavior of using tax technology between accounting tax volunteers and non-accounting tax volunteers. The research method used in this study is a quantitative method and the type of data used is primary data in the form of questionnaire results that have been distributed to respondents. The sample in this study is 90 tax volunteers in Jember district with 45 of them accounting tax volunteers and 45 other non-accounting tax volunteers. The data collection technique is purposive sampling. The data analysis methods used were descriptive analysis and independent sample t-test analysis. The results of this study show that there is no difference between accounting tax volunteers and non-accounting tax volunteers regarding the behavior of using tax technology. Further research is expected to be able to examine related to the behavior of using tax technology with a wider object.